2017
DOI: 10.1523/jneurosci.1339-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Decreases the Gain of Visual Responses in Awake Macaque V1

Abstract: Serotonin, an important neuromodulator in the brain, is implicated in affective and cognitive functions. However, its role even for basic cortical processes is controversial. For example, in the mammalian primary visual cortex (V1), heterogenous serotonergic modulation has been observed in anesthetized animals. Here, we combined extracellular single-unit recordings with iontophoresis in awake animals. We examined the role of serotonin on well-defined tuning properties (orientation, spatial frequency, contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 90 publications
6
44
4
Order By: Relevance
“…Finally, a previous study in monkey V1, using single cell recordings and pharmacological 5-HT1B and 5-HT2A receptor activation via microiontophoresis in anaesthetized preparations, revealed effects on both spontaneous activity and response gain (Shimegi et al, 2016). In contrast to ours and the above study, where the additional subtractive component essentially contributed to contrastgain control at lower contrast, a more recent study in monkey V1 found, however, for the majority of recorded cells only divisive scaling of evoked responses (Seillier et al, 2017). As their recordings were done in awake monkeys, these differences may indeed reflect principal changes in cortical state and 5-HT levels during wakefulness (Portas et al, 2000;Tyree et al, 2017) and/or species-specific differences in individual 5-HT receptor sets ("receptomes") tailored to task-specific demands on signal integration.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Finally, a previous study in monkey V1, using single cell recordings and pharmacological 5-HT1B and 5-HT2A receptor activation via microiontophoresis in anaesthetized preparations, revealed effects on both spontaneous activity and response gain (Shimegi et al, 2016). In contrast to ours and the above study, where the additional subtractive component essentially contributed to contrastgain control at lower contrast, a more recent study in monkey V1 found, however, for the majority of recorded cells only divisive scaling of evoked responses (Seillier et al, 2017). As their recordings were done in awake monkeys, these differences may indeed reflect principal changes in cortical state and 5-HT levels during wakefulness (Portas et al, 2000;Tyree et al, 2017) and/or species-specific differences in individual 5-HT receptor sets ("receptomes") tailored to task-specific demands on signal integration.…”
Section: Discussioncontrasting
confidence: 97%
“…In addition, direct cortical application of 5-HT via microiontophoresis and single cell cortical recordings in vivo showed either suppressive or facilitative effects (Krnjevic and Phillis, 1963;Reader, 1978;Waterhouse et al, 1990). More recent studies applied antagonist and agonist of 5-HT via microiontophoresis in the monkey visual cortex, suggesting that 5hydroxytryptamin (5-HT)-receptors are involved in normalization of visual responses (Watakabe et al, 2009;Seillier et al, 2017). However, so far, only studies on somatosensorydriven behavioral responses (Dugué et al, 2014) and in olfactory cortex (Lottem et al, 2016) specifically activated 5-HT neurons in the DRN to trigger the natural and intrinsic spatiotemporal synaptic 5-HT innervation pattern within the target cortical areas.…”
Section: Introductionmentioning
confidence: 99%
“…Hz) during awakening [8,9] to maintain the arousal state by acting on the hypothalamus [10,11] and cerebral cortex [12,13]. Serotonergic neurons project to the cerebral cortex including visual areas [14][15][16] and are known to modulate neuronal visual responses via various kinds of 5-HT receptor subtypes [17][18][19][20]. For example, Waterhouse et al (1990) reported that iontophoretically-administered serotonin decreases the signal-to-noise ratio of the neuronal activities in the primary visual cortex (V1) of anesthetized rats [17].…”
Section: Introductionmentioning
confidence: 99%
“…While 5HTR1 is inhibitory, 5HTR2 is excitatory. Recent findings point to a more sophisticated role of these receptors when investigating response curves of cortical processing as done in the visual cortex (Shimegi et al, 2016;Seillier et al, 2017) and we propose that 5HT alters the signal processing in the mPFC in a similar way.…”
Section: The Action Of 5htr1 and 5htr2 Receptors In The Mpfcmentioning
confidence: 75%